Modern Integration Units: Comparative Analysis Of The Growth Factors - Khusainov, Bulat Doskalievich; Shelomentsev, Andrey Gennadyevich; Doroshenko, Svetlana Viktorovna (Economy of Regions, 2015)
In the article, the results of the research, which purpose is to ground and assess the factors of economic growth of regional integration communities and national economies of member countries that develop them, are presented. The foreign trade, mutual trade turnover, and domestic demand are allocated as such factors. The authors has applied the novelty in their methodology which in contrast to the traditional assessment method of growth factors of integration communities and their participants, is based on comparison of two components - external and domestic demand, based on dividing the external demand on two components: the first one is pure export (the difference between export and import is a component of cumulative demand) of goods in integration community, i.e. the pure export of mutual trade; the second one is a pure export of foreign trade of goods outside of the integration association. Scope of the research is seven most known regional integrated units arose at different times and being at different stages of development - the European Union, North American Free Trade Area, Association of Southeast Asian Nations, Southern American Common Market, Asia-Pacific Economic Cooperation, and also member countries of the Eurasian integration - the Customs Union and Common Free Market Zone developed into the Eurasian Economic Union in January 1, 2015. In conclusion, it is noted that the integration develops successfully only in the conditions of the rise in national economies of the participating countries. Crisis economies have to deal more with internal problems than to resolve integration issues.